Recombinant system for overexpression of cholera toxin B subunit in Vibrio cholerae as a basis for vaccine development. - Sanchez, J (1989)
We have constructed an overexpression system in which the gene encoding the B subunit of cholera toxin (CTB) was placed under the control of the strong tacP promoter in a wide host range plasmid. Recombinant nontoxigenic classical and E1 Tor Vibrio cholerae strains of different serotypes harboring this plasmid excreted 10- to 100-fold higher amounts of CTB than any other wild-type or recombinant strain tested and may therefore be useful killed oral vaccine strains. The manipulations to place the CTB gene under tacP also included, by design, the introduction of single enzyme restriction sites for gene fusions to the CTB amino terminus. Cloning into these sites allows construction of CTB-derived hybrid proteins carrying various putative vaccine peptide antigens.